Pembuatan Motion Graphic Program Konselor Sebaya Tim Bimbingan Konseling IPB: The Making of Peer-Counselor Program’s Motion Graphics of IPB University Counseling Center - Amata Fami; Fathny Syafa Rasyidah (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2020)
ABSTRACTThe Guidance and Counseling Team of the Bogor Agricultural Institute (TBK-IPB) is a team that provides services in the form of guidance and counseling for students at IPB. TBK-IPB facilitates students to be able to adjust to campus life so that they can achieve optimal academic performance and are able to plan a good career achievement in the future. TBK-IPB has a peer counselor or story partner program to help listen to student problems who feel uncomfortable consulting with senior counselors/counselor lecturers. In order to disseminate information about the peer counseling program to IPB students, a product (motion graphics) that is informative, interesting and easy to distribute is needed. The methods used in the manufacture of motion graphics products are Development, Preproduction, Production, Postproduction and Delivery. The result is a product with a video format, loaded with images, text and audio that is easy to share via social media. ABSTRAKTim Bimbingan dan Konseling Institut Pertanian Bogor (TBK-IPB) adalah tim yang memberikan layanan berupa bimbingan dan konseling kepada mahasiswa di IPB. TBK-IPB memfasilitasi mahasiswa agar dapat menyesuaikan diri dengan kehidupan kampus sehingga mencapai prestasi akademik yang optimal dan mampu merencanakan pencapaian karir yang baik di masa yang akan datang. TBK-IPB memiliki program konselor sebaya atau teman cerita untuk membantu mendengarkan permasalahan mahasiswa yang merasa belum nyaman berkonsultasi dengan konselor senior/dosen konselor. Dalam rangka menyebarkan informasi mengenai program konselor sebaya kepada mahasiswa IPB, dibutuhkan sebuah produk (motion graphics) yang informatif, menarik dan mudah dalam distribusinya. Metode yang digunakan dalam pembuatan produk motion graphics ini adalah Development, Preproduction, Production, Postproduction dan Delivery. Hasilnya adalah sebuah produk berformat video, memiliki muatan gambar, teks dan audio yang mudah disebarkan via media sosial. Kata kunci: Motion Graphics, Tim Bimbingan Konseling, Bimbingan dan Konseling, Konselor Sebaya